Collaborative teaching: enhancing understanding of Hazardous Chemical regulations / Amin Aadenan ... [et al.]. - Aadenan, Amin; Ahmad, Mardiana; Md Rashid, Siti Nafisah; Azman, Nur Helmi @ Nur Jannah; Hashim, Rohasmizah; Badar Sher, Mohamad Noor (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Understanding the safe handling of hazardous chemicals is important among students as it helps to prepare the safety expectations and protocols they will encounter in their future workplaces. The Occupational Safety and Health Regulations (Classification, Labelling and Safety Data Sheet of Hazardous Chemicals) 2013, commonly referred to as the “CLASS 2013” regulations, are a set of regulations in Malaysia aimed at ensuring the safe handling of hazardous chemicals. The CLASS 2013 Regulations are important for students as they prepare them for safe chemical handling, ensure compliance with legal standards, foster a safety culture, improve efficiency and productivity, enhance career prospects, and promote personal well-being and safety.